Storage and Packaging Evaluation for Preserving Polyphenols in Black Garlic - Nurriyanti, Anggita Halimah; Mardawati, Efri; Nurhasanah, Siti; Nurliasari, Desy (Universitas Diponegoro, 2024)
Black garlic (Allium sativum L.) is produced through a controlled thermal aging process, enhancing its phenolic and flavonoid content and increasing antioxidant, anti-inflammatory, and anticancer properties. This study aimed to evaluate the effects of different storage temperatures (30°C, 35°C, and 40°C) and packaging materials (paper core–PC and aluminum foil–AF) on the stability of these bioactive compounds. Black garlic was prepared by aging single clove garlic at 74°C for 12 days using a fermenter. The aged garlic was then packaged in PC and AF and stored under specified conditions. Total phenolic content (TPC) was determined using the Folin-Ciocalteu method, while total flavonoid content (TFC) was measured with the aluminum chloride colorimetric method. Results indicated that higher storage temperatures led to an insignificant reduction in both phenolic and flavonoid contents, with AF packaging providing better retention due to its superior barrier properties (TPC = 2.62–3.51 mg GAE/g and TFC = 1.57–2.09 mg QE/g). At 35°C, PC packaging also showed comparable performance, suggesting its potential as a sustainable alternative (TPC = 2.92 mg GAE/g and TFC = 2.09 g QE/g). The study highlights the importance of optimizing storage conditions and packaging materials to preserve the functional properties of black garlic. These findings provide valuable insights for the food industry in developing effective storage strategies to enhance the benefits of black garlic.